Pink Eye Cases in Sheep at UD. Peternakan Boerstud Kambing Boerja, Malang - Dyah Laksito Rukmi; Riski Bagda Maulida; Nurkholis Nurkholis; Erfan Kustiawan; Dharwin Siswantoro (Journal of Applied Veterinary Science And Technology, 2022)
Background: Pink Eye was an eye disease that can be transmitted to livestock either by direct contact with infected livestock as well as through vectors of flies, dust, and water. Pink Eye can cause chronic cases and lasts all year round. This causes losses to farmers starting from decreased appetite which results in weight loss and even to the death of livestock. Purpose: The purpose of this case study was to provide information on efforts to prevent and treat Pink Eye disease in UD. Peternakan Boerstud Kambing Burja, Malang. Method: The methods used include collecting primary data in the field while secondary data is obtained from record book the UD. Peternakan Boerstud Kambing Burja, Malang. The prevalence of Pink Eye events from September-December 2021 shows that as many as 55 out of 110 sheep or 50% of the total sheep population are infected with Pink Eye disease. Results: The healing process of Pink Eye is carried out by carrying out treatment consistently with the administration of oxytetracycline eye ointment which is topically applied in the morning and evening. The period of time required for the healing process for 3 days depends on the severity of the infection. Conclusions: The recovery of the eyes of sheep infected with Pink Eye by 100%.